2011
DOI: 10.1007/s11104-011-0826-7
|View full text |Cite
|
Sign up to set email alerts
|

Water-deficit tolerance in citrus is mediated by the down regulation of PIP gene expression in the roots

Abstract: Water deficit (WD) is a growing problem in agriculture. In citrus crops, genetically-determined rootstock characteristics are important factors influencing plant responses to WD. Aquaporins are involved in regulating the water supply to the plant by mediating water flow through the cell membranes. Recent studies support a direct role for aquaporins in plant water relations and demonstrate their involvement in WD tolerance. This study investigates the relationship between photosynthetic and water-balance parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 91 publications
2
22
0
Order By: Relevance
“…8, under short-term salt stress, the transcriptional levels of SbPIP1;6, SbPIP2;2, and SbPIP2;6 were upregulated by Si. Previous studies have shown either decreases or increases in aquaporin activity under stress conditions in different plants (Hachez et al, 2012;Vandeleur et al, 2009;Rodriguez-Gamir et al, 2011). Our result was consistent with previous studies showing that the upregulation of aquaporin aids salt resistance (Qian et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…8, under short-term salt stress, the transcriptional levels of SbPIP1;6, SbPIP2;2, and SbPIP2;6 were upregulated by Si. Previous studies have shown either decreases or increases in aquaporin activity under stress conditions in different plants (Hachez et al, 2012;Vandeleur et al, 2009;Rodriguez-Gamir et al, 2011). Our result was consistent with previous studies showing that the upregulation of aquaporin aids salt resistance (Qian et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Treeby et al [78] investigated irrigation management and rootstock effects on navel orange and reported that irrigation management is far more critical for external fruit quality for trees on sweet orange and, to a lesser extent, trees on the citranges compared to trees on trifoliate orange and Cleopatra mandarin.…”
Section: Droughtmentioning
confidence: 99%
“…reshni Hort exTan.) and one of their hybrids, subjected to moderate water deficit [ 21 ], and in roots of P . trifoliata , Cleopatra mandarin and Carrizo citrange ( C .…”
Section: Introductionmentioning
confidence: 99%